PENGARUH MEDIA SOSIAL TWITTER TERHADAP MINAT BACA BERITA ONLINE FOLLOWER AKUN @DETIKCOM DI PEKANBARU - MAYANGSARI, RAISHA DWI; ", RUMYENI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Social media is currently quite popular among the people. Same as the mass media, social media can also disseminate information to the public at large. One of social media that is currently popular is twitter. Most Internet users today have twitter which is helps them to interact with each other. The users access the site to get the latest news every week and social media is a place or means to connect people to interact. The mass media present news desirable audience through twitter that the public interest in the online news will increase. The purpose of this research is to determine how much influence social media Twitter on reading online news follower @detikcom in Pekanbaru.The method used in this study is a quantitative method. Researchers collected data using questionnaires and documentation. The location of this research is in Kota Pekanbaru. The number of samples for this study as many as 96 respondents, using sampling techniques unknown population because the population of followers @detikcom in Kota Pekanbaru is not known for certain. To determine the effect of these two variables, researchers used a simple linear regression analysis. While the questionnaire for processing test data, performed using the Statistical Product and Service Solutions ( SPSS ) Windows version 17.Based on a simple linear regression to study the influence of social media Twitter on reading online news follower @detikcom in Kota Pekanbaru, the regression coefficient values obtained in this study is Y = 2.543 + 0.721 X with a significance level of 0.000 and smaller than Î± = 0.05. While based on the determination test, the result is 50.8 %. That is mean, there is the influence of social media Twitter on reading online news follower @detikcom in Pekanbaru. The percentages show that social media affects the reading Twitter followers to read online news posted by @detikcom account with medium category. That means, the dominant respondents using twitter as a means of receiving information. Twitter also gives benefits to @detikcom to spread the news, so that reading the follower is increasing with the news posted by that user via twitter. Thus, Ho is rejected and Ha accepted.Keywords: Social Media, Online News, Interest